PROSES KELEMBAGAAN DAN PERATURAN PEMERINTAH PADA LEMBAGA AMIL ZAKAT - Bonita Almira Putri; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This study is aimed to shows and identification of Amil Zakah Institution responses about management of zakah rules by governance in strategic responses to institutional processes views. The researcher also want to see the LAZ perspectives about the changes of the regulations which is being problem for the past a year in Indonesia. Research approch is qualitative approach explanatory. Data collection interviews with the informants in case study object. Object of this research is LAZ YDSF Surabaya because they are the oldest inEast Java Province and is founded in Surabaya. Technique analysis is using descriptive narrative and pairing pattern. This research shows that LAZ YDSF is not include in acquiesce response, because there are some regulations that needed to be compromised with the government. Purpose of this research is want to see a new perspective from Amil Zakah Institutions in Indonesia in order to make the best coordination and sinergisity with government to build a better country REFERENCESBeik, Irfan Syauqi dan Laily Dwi. 2016. Ekonomi Pembangunan Syariah. Edisi Revisi.Depok: PT Rajagrafindo Persada.Creswell, John. W. 2015. Research Design Second Edition. Terjemahan oleh Lintan Lazuardi. Yogyakarta: Pustaka Pelajar. Dawson, Yelena. 2015. The Institutionalisation of Private Sector Performance Masurement in an Australian Oot-forprofit Organisation. epublications@scu. Fakultas Bisnis Administrasi. Southern Cross University.Fauzia, Amelia. 2008. Faith and a State: a History of Islamic Philanthropy in Indonesia. Disertasi tidak diterbitkan. Melbourne Faculty of Arts University of Melbourne.Hilmi, Hasbullah. 2012. Dinamika Pengelolaan Wakaf Uang: Studi Sosio-Legal Perilaku Pengelolaan Wakaf Uang Pasca Pemberlakuan UU No. 41 Tahun 2004 Tentang Wakaf. Ijtihad, Jurnal Wacana Hukum Islam dan Kemanusiaan, Vol. 12, No. 2 (12).Huda, Nurul, dkk. 2012. Kebijakan Publik Islami. Jakarta: Kencana Prenada Media Group.Kamil, Syukron. 2016. Ekonomi Islam, Kelembagaan, dan Konteks Keindonesiaan. Depok: PT Rajagrafindo Persada.Karim, Adiwarman Azwar. 2010. Sejarah Pemikiran Ekonomi Islam. Edisi Ketiga. Jakarta: Rajawali Press.Khairinisa, Dini. 2012. Proses Konstruksi Perkembangan Organisasi Zakat (Studi pada Dompet Dhuafa Republika). Jakarta: UI Library.LAZ YDSF,. Profil LAZ, (Online), (www.ydsf.org 20 November 2016. (20.17)                                                                                                                                                                                                                                                                                Muhammad, dan Abu Bakar. 2011. Manajemen Organisasi Zakat. Malang: Madani Wisma Kalimetro.Modell, S. (2001). Performance Measurement and Institutional Processes: A Study of Managerial Responses to Public Sector Reform. Management Accounting Research, 12: 439, 441.Nafik, Muhammad dan Hazami Bashlul. 2016. Peran dan Implementasi Wakaf dalam Peningkatan Kesejahteraan Masyarakat. Inferensi Junral Penelitian Sosial dan Keagamaan. Vol 10 No.1:Oates, Grainne. 2013. Exploring the Links between Stakeholder Type, and Strategic Response to Stakeholder and Institutional Demands in the Public Sector Context. International Journal of Business and Management; Vol. 8, No. 21: 51-52.Oliver, C. (1991). Strategic Responses to Institutional Processes. Academy of Management Review Journal, 16, 146-163.Qardhawi, Yusuf. 1996. Hukum Zakat. Bogor: Pustaka Lintera Antar Nusa.Qardhawi, Yusuf. 2005. Spektrum Zakat dalam Membangun Ekonomi Kerakyatan. Jakarta: Zaikrul Hakim.Republik Indonesia. Undang-Undang No 38 Tahun 1999 tentang Pengelolaan Zakat. 1999: Kementerian Agama.---------------------------. Undang-Undang No 23 Tahun 2011 tentang Pengelolaan Zakat. 2011: Diperbanyak oleh BAZNAS.---------------------------. PP No 14 Tahun 2014 tentang Penjelasan UU No 23 Tahun 2011 Pengelolaan Zakat. 2014: Diperbanyak oleh BAZNAS.Romanelli, Elaine. The New Instituitonalism in Organizational Analysis by Powell and Dimaggio Review. The Academy of Management Review Journal, Vol. 17, No. 3 (Jul., 1992), 612-614.Rosyidah, Trie A dan Asfi Manzilati. 2014. Implementasi Undang-Undang Nomor 23 Tahun 2011 terhadap Legalitas Pengelolaan Zakat oleh Lembaga Amil Zakat (Studi pada Beberapa LAZ di Kota Malang). Malang: Universitas Brawijaya). UB.Sudarwati, Yuni dan Nidya Waras Sayekti. 2011. Jurnal Ekonomi & Kebijakan Publik, Vol. 2, No. 1, (Juli): 578-581Wahyuni, Ersa Tri. 2013. The Role of Entrepreneur in IFRS Diffusion: The Case Study of Convergence IFRS in Indonesia. Yin, Robert K. 2014. Case Study Research: Design and Method. Terjemahan oleh M. Djauzi Mudzakir. Jakarta: PT Rajagrafindo Persada.Yustika, Ahmad Erani. 2013. Ekonomi Kelembagaan. Paradigma, Teori, dan Kebijakan. Jakarta: Penerbit Airlangga.